New events in top performance sports: Potential benefit, challenge, risk, or hazard - Leithäuser, R. M.; Beneke, R. (International Journal of Sports Physiology and Performance, 2025)
There is no doubt that top sporting events attract huge crowds of spectators, on-site in sporting arenas, on television, or on social media. Sports is a massive business and a huge global money-making industry. Therefore, it is no surprise that various stakeholders of this industry try to come up with new sporting events and formats to promote the sports, generate additional media attention, and ultimately make more income.